Letter to Rita Dobson from Delores Elwell - Delores Elwell:::::: (1976)
This letter, dated March 9, 1976, is from the Mediodia Business and Professional Women's Luncheon Club of Oxnard to Mrs. Rita Dobson, Chairman of Political Promotion. The club formally endorses Jane Tolmach, a member of Oxnard BPW, as a candidate for the 36th Assembly District. The letter notes that the incumbent is not seeking re-election, making it an opportune time to support her candidacy. The club expresses confidence that Mrs. Tolmach is highly qualified for the office. The endorsement is signed by Delores Elwell, President, with a copy sent to Jane Tolmach.